Evaluation of Imprint and Multi‐Level Dynamics in Ferroelectric Capacitors - Sara Vecchi; Francesco Maria Puglisi; Pascal Appelt; Roberto Guido; Xuetao Wang; Stefan Slesazeck; Thomas Mikolajick; Suzanne Lancaster (Advanced Electronic Materials)
Abstract Fluorite‐structured ferroelectrics are one of the most promising material systems for emerging memory technologies. However, when integrated into electronic devices, these materials exhibit strong imprint effects that can lead to a failure during writing or retention operations. To improve the performance and reliability of these devices, it is cardinal to understand the physical mechanisms underlying the imprint during operation. In this work, the comparison of First‐Order Reversal Curves measurements with a new gradual switching experimental approach named “Unipolar Reversal Curves” is used to analyze both the fluid imprint and the time‐dependent imprint effects within a 10 nm‐thick Hf0.5Zr0.5O2 capacitor. Interestingly, the application of delay times (ranging from 100 µs up to 10 s) between the partial switching pulses of a Unipolar Reversal Curve sequence enables analysis of the connection between the two aforementioned imprint types. Based on these results, the study finally reports a unified physical interpretation of imprint in the context of a charge injection model, which explains both types of imprint and sheds light on the dynamics of multi‐level polarization switching in ferroelectrics.